1989
DOI: 10.1002/acp.2350030103
|View full text |Cite
|
Sign up to set email alerts
|

The applicability of verbal mnemonics for different populations: A review

Abstract: The main aims of this review were to assess(1) the likelihood of learners making spontaneous use of verbal mnemonics, and (2) the extent to which learners will benefit from using verbal mnemonics. Over 60 investigations of verbal mnemonics were reviewed, most of which concentrated upon sentence mnemonics or first-letter mnemonics; although many of the studies used students as subjects, the review also considers the value of verbal mnemonics for schoolchildren, mentally handicapped people, brain-injured patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 74 publications
1
8
0
1
Order By: Relevance
“…Also, notice that both of these mnemonics are of the same type; both leverage the "first letter of a word" to recall a fact. This finding is consistent with the finding that first-letter based mnemonics have frequent spontaneous use relative to other types of mnemonics and that they are effective for learning inter-related pieces of information (Boltwood and Blick 1970;Cook 1989).…”
Section: Usage and Helpfulness Of Mnemonicssupporting
confidence: 90%
See 3 more Smart Citations
“…Also, notice that both of these mnemonics are of the same type; both leverage the "first letter of a word" to recall a fact. This finding is consistent with the finding that first-letter based mnemonics have frequent spontaneous use relative to other types of mnemonics and that they are effective for learning inter-related pieces of information (Boltwood and Blick 1970;Cook 1989).…”
Section: Usage and Helpfulness Of Mnemonicssupporting
confidence: 90%
“…The efficacy of first-letter based mnemonics depends on the nature of the materials to be learned (Cook 1989). When sets of unrelated words were learned, first-letter mnemonics did not enhance performance relative to study with no particular instruction; however, when learning sets of related words, firstletter mnemonics did enhance performance.…”
Section: Potential Benefits Of Mnemonicsmentioning
confidence: 94%
See 2 more Smart Citations
“…Mnemonics are rightly considered to improve data acquisition and recall,5 to facilitate understanding,6 to improve motivation and enjoyment,7 while supplying integration, meaning and cues where none existed 3. The effectiveness of the Advanced Cardiac Life Support mnemonics ‘4Hs’ and 4Ts’ and ‘EMD aide’ have been compared in a randomised trial, which showed an advantage for the latter 2.…”
Section: Introductionmentioning
confidence: 99%